Tuberculosis Problem In Dakahlia Governorate, Egypt - Aal, Amina Mostafa Abdel; El-Mashad, Noha; Magdi, Dalia (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
Tuberculosis (TB) is a potentially fatal contagious disease that can affect almost any part of the body but is mainly an infection of the lungs. It has been present in humans since antiquity. In the past, tuberculosis has been called consumption, because it seemed to consume people from within, with a bloody cough, fever, pallor, and long relentless wasting. In Egypt, TB constitutes the second most important public health problem after schistosomiasis. Although Egypt has relatively low levels of TB according to data from the World Health of Organization, 2005:66% of TB cases occur among the socially and economically productive age groups of 15 to 54 years. According to Ministry of Health and Population (MOHP), Egypt; tuberculosis control is carried out through 111 chest centers and 39 chest disease hospitals. Treatment failure accounts for 3%–5%of the treatment outcome of new smear positive cases and 13%–17% of retreated cases and this is due to non-compliance to treatment, defi cient health education to the patient, poor patient knowledge regarding the disease and diabetes mellitus as co-morbid. The incidence and prevalence of tuberculosis in Egypt has been declining due to increased efforts of the MOHP. Prevalence dropped from 88/100,000 population in 1990 to 24 in 2008, according to data from WHO. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2013; X(1); 43-49 DOI: http://dx.doi.org/10.3126/saarctb.v10i1.8677